2005
DOI: 10.1207/s15374424jccp3403_8
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Assessment of Autism Spectrum Disorders in Children and Adolescents

Abstract: This article reviews evidence-based criteria that can guide practitioners in the selection, use, and interpretation of assessment tools for autism spectrum disorders (ASD). As Mash and Hunsley (2005)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
252
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(267 citation statements)
references
References 144 publications
3
252
0
2
Order By: Relevance
“…Social behavior and related parameters were analyzed along two axes, skills or abilities (e.g., adaptive socialization skills) and problem/aberrant behavior (e.g., social withdrawal), which were related to central ''gold standard'' measures of autistic behavior (e.g., ADI-R) and to DSM-IV diagnostic criteria. Supporting this scheme are our findings of parallel continua of severity of the aforementioned social behavior parameters and autistic behavior impairment by DSM-IV/ADI-R , and current views on evidence-based research on idiopathic ASD [Ozonoff et al, 2005].…”
Section: Subjectssupporting
confidence: 62%
“…Social behavior and related parameters were analyzed along two axes, skills or abilities (e.g., adaptive socialization skills) and problem/aberrant behavior (e.g., social withdrawal), which were related to central ''gold standard'' measures of autistic behavior (e.g., ADI-R) and to DSM-IV diagnostic criteria. Supporting this scheme are our findings of parallel continua of severity of the aforementioned social behavior parameters and autistic behavior impairment by DSM-IV/ADI-R , and current views on evidence-based research on idiopathic ASD [Ozonoff et al, 2005].…”
Section: Subjectssupporting
confidence: 62%
“…Finally, the child had to meet criteria for a diagnosis of either Autism or Autism Spectrum Disorder on the Autism Diagnostic Observation Schedule-General (ADOS-G; Lord et al 2002), Module 4. The ADOS-G is a gold standard of ASD evaluation (Ozonoff et al 2005), and trained members of the PEERS team who had established ADOS coding reliability completed administration of the ADOS-G. Of note, given that this study was commenced prior the publication of the DSM-5, it is not clear whether all participants would meet new criteria for an ASD diagnosis given the required presence of restricted or repetitive interest and behaviors. An additional requirement was that teens not have comorbid severe mental health disorders (e.g., psychotic disorders).…”
Section: Randomization and Inclusion Criteriamentioning
confidence: 99%
“…Parenting stress as assessed by the SIPA has been found to relate to the quality of parents' perceptions of their parenting alliance, other psychological measures of adolescent and parent functioning, and the quality of the marital relationship and family system (Sheras et al 1998). Ozonoff et al (2005) identified the SIPA as a psychometrically sound measure for use with parents of adolescents with ASD. Within this study, Cronbach's alpha suggested strong internal consistency (.95) at pre and post intervention.…”
Section: Stress Index For Parents Of Adolescents (Sipa)mentioning
confidence: 99%
“…3 Behavioral intervention is more effective the earlier it is initiated. [4][5][6][7] Therefore, the identification of biological markers of autism would have a number of ramifications: markers could assist in the early and accurate diagnosis of the disorder; they may identify particular biological targets for treatment; and they could be used to define subgroups for specific treatments as well as for genetic studies.…”
Section: Introductionmentioning
confidence: 99%